Resiliensi pada Wanita Minangkabau Dewasa Madya Setelah Kematian Pasangan Hidup - Widya Monica; Rinaldi Rinaldi (RC-INSTITUT, 2020)
The purpose of this study was to determine the resilience of middle adult Minangkabau women after the death of a spouse. This research uses qualitative research methods using a phenomenological approach through observation and interview methods. The criteria for the informants of this study were middle adult Minangkabau women who were widowed because of the death of their husbands. Middle adult Minangkabau women who experience the death of their partner initially have deep feelings of sadness, feelings of distrust, and even loss of motivation to live. After some time and influenced by several factors that influence resilience, namely individual factors, family factors and community factors, finally the subject can become a resilient individual. The subject can take the positives of the problem, make the subject able to empathize and make the subject often interact with their environment and also often do positive things.